Type 2 diabetes clusters in the Novosibirsk region - I. A. Bondar; O. Y. Shabelnikova (Сахарный диабет)
BACKGROUND: Type 2 diabetes mellitus (T2DM) is a heterogeneous disease. Determination of different T2DM phenotypes will improve the prediction of metabolic disorders, the risk of complications and individual diabetes therapy.AIM: To identify clusters of T2DM in patients with different duration of diabetes with a study of the frequency of diabetic complications and drug therapy in the Novosibirsk region.MATERIALS AND METHODS: The study was carried out at Diamodul in the period 2013–2017 in the Novosibirsk region. K-means cluster analysis was performed in 2805 T2DM patients aged 44 to 75 years with a duration of diabetes of 7.84±6.53 years based on 5 variables — HbA1c, age at diagnosis, BMI, C-peptide, sex.RESULTS: Cluster analysis identified three clusters: cluster 1 in 1003 patients (35.7%) with preserved β-cell function, age of T2DM diagnosis 51.72±8.29 years and BMI 33.50±5.74 kg/m2, in men there was a 27% higher risk of developing diabetic nephropathy compared to women. Cluster 2 in 432 patients (15.4%) with increased function of β-cells, the age of diagnosis of T2DM was older — 52.91±7.75 years, patients had a higher BMI of 35.64±7.21 kg/m2 and more high diastolic blood pressure, earlier development of diabetic retinopathy, nephropathy and polyneuropathy, and better response to metformin therapy and combined therapy with metformin and sulfonylurea. Cluster 3 in 1370 patients (48.8%) with reduced function of β-cells, the age of diagnosing T2DM was younger — 49.63±8.32 years, patients had a lower BMI of 33.09±6.36 kg/m2 and had longer diabetes, high fasting glucose levels, males were associated with a higher risk of developing diabetic nephropathy (by 26%) compared with women, the first line of therapy was insulin therapy in 52.8% of patients.CONCLUSION: The conducted study in T2DM patients with different duration of diabetes confirmed the possibility of using cluster analysis to identify phenotypes of T2DM in the Russian population by five variables (HbA1c, age at the time of diagnosis, BMI, C-peptide, gender). A high incidence of early development of diabetic polyneuropathy, nephropathy and retinopathy was revealed in a cluster with increased function of β-cells, male gender was risk factor for diabetic nephropathy and polyneuropathy.